2019
DOI: 10.26434/chemrxiv.8792177.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid Online Buffer Exchange: A Method for Screening of Proteins, Protein Complexes, and Cell Lysates by Native Mass Spectrometry

Abstract: It is important to assess the identity and purity of proteins and protein complexes during and after protein purification to ensure that samples are of sufficient quality for further biochemical and structural characterization, as well as for use in consumer products, chemical processes, and therapeutics. Native mass spectrometry (nMS) has become an important tool in protein analysis due to its ability to retain non-covalent interactions during measurements, making it possible to obtain protein structural info… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…This is advantageous for protein complexes that are difficult to express or purify and only available in small quantities. An alternative technique that can be used for the desalting of protein complexes is rapid online buffer exchange, which has shown the ability to remove nonvolatiles from different buffer conditions . However, submicrometer capillaries can be used when HPLC equipment is unavailable and if high throughput is not needed.…”
Section: Resultsmentioning
confidence: 99%
“…This is advantageous for protein complexes that are difficult to express or purify and only available in small quantities. An alternative technique that can be used for the desalting of protein complexes is rapid online buffer exchange, which has shown the ability to remove nonvolatiles from different buffer conditions . However, submicrometer capillaries can be used when HPLC equipment is unavailable and if high throughput is not needed.…”
Section: Resultsmentioning
confidence: 99%
“…During heating, the unfolding of the monomer causes loss of the helical structure and allows the Cys121 to reversibly create a Cys106–Cys121 disulfide and a free thiol at Cys 119, which induces the aggregation . In order to maintain the interface of the BLG dimer and minimize overall structural change, we optimized the reduction conditions by monitoring the mass shift of the proteins with online buffer exchange native MS. , We found that in 50 mM dithiothreitol, after 20 min incubation at 50 °C, the average mass increased by 2 Da for each subunit after reduction (Figure S2) which indicates the reduction of only one disulfide bond. Presumably only the water-accessible disulfide bond Cys66–Cys160 has undergone reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Accurate masses were measured on an Exactive Plus EMR Orbitrap instrument (Thermo Scientific) modified with a quadrupole mass filter and a surface-induced dissociation device . The samples were injected on a self-packed buffer exchange column (Bio-Rad P 6̅ packing material) using an Ultimate 3000 RSLC (Thermo Scientific) coupled to the modified Exactive Plus EMR Orbitrap instrument (Thermo Scientific). , The mobile phase was 200 mM ammonium acetate. The flow rate was 100 μL/min, and proteins typically eluted within 1.2 min.…”
Section: Methodsmentioning
confidence: 99%